IMPLEMENTASI NILAI KARAKTER PEDULI LINGKUNGAN DI SD TAKHASSUS AL-QURAN KALIBEBER WONOSOBO - Fighyatutsania, Syita; Nasokha, Nasokha; Rois, Ahmad (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
One of the important to familiarize students with environmental care character values as form to caring for environmental. The purpose of the research that is to find out the application care character values to, to find out what forms of environmenta care character value activities are carried out by students, to find out the obstacles that occur during the implementation of environmental care character values. This research is the type descriptive qualitative, while the data collection techniques used is the observation method, interview method and documentation. After the data was collected, it was data model data analysis for Miles and Hubermen, namely by data reduction, data presentation, and make a conclusions. The result of this show (1) The value to the environmental care character of the students at the SD Takhassus Al-Qur’an was included in the very good category because almost all of the students do activities the environmental care character value. (2the form of a caring for the enviromental thats begins with habituations of carrying garbage as a school has a very good category because this activity becomes a daily routine in the school environmental or in the dormitory. (3) Constraints and solutions to the character values of character care enviromental for students through environmental care habituation activites at SD Takhassus Al-Qur’an Elementary School, namely the lack of supervision, conditioning, and evaluation carried out by the teachers at SD Takhasssus Al-Qur’an Elementary School.